XGLM-564M and RoBERTa Performance in Low-Resource Educational Dialogue Classification - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 11 peer-reviewed papers addressing the following research question: How does the performance of XGLM-564M on low-resource educational dialogue act classification compare to RoBERTa in Indonesian and English, measured by F1 scores on imbalanced datasets. 10 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.2/10. This report is a machine-
Machine-generated literature synthesis.